2017
DOI: 10.1093/eurpub/ckx043
|View full text |Cite
|
Sign up to set email alerts
|

Malnutrition and birth related determinants among children in Qazvin, Iran

Abstract: Little is known about the effect of birth weight, birth order and number of siblings on the nutritional status in children in Iran, especially in Qazvin province. The aim of this study was to provide the current data on malnutrition and birth related determinants among children in Qazvin, Iran. This study was conducted in six cities of Qazvin province (Iran), during December 2009-December 2010. Data on age, weight and height were taken and birth weight, number of children in family, birth order, parental caree… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 15 publications
1
19
0
3
Order By: Relevance
“…A previous study reported that a larger number of siblings increased the odds ratio for thinness for girls but not for boys [23]. By contrast, one study showed no relationship between the number of siblings or birth order and thinness [24].…”
Section: Introductionmentioning
confidence: 84%
See 1 more Smart Citation
“…A previous study reported that a larger number of siblings increased the odds ratio for thinness for girls but not for boys [23]. By contrast, one study showed no relationship between the number of siblings or birth order and thinness [24].…”
Section: Introductionmentioning
confidence: 84%
“…Other studies indicated that having a larger number of siblings was associated with a more significant decrease in BMI [18,31]. One study, however, reported that there was no association between the number of siblings and thinness [24], whereas another study found that thinness was more common in girls than in boys [23]. One possible explanation is the effect of behavior and interaction among family members.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding birth order, a higher birth order has been reported to signi cantly increase ORs for undernutrition [20][21][22]36], which is consistent with our results. In contrast, some studies have not found a relationship between BMI or thinness and birth order [24,32]. Thus, the association of birth order with childhood thinness remains unclear; however, differences in fetal nutrition and changes in some factors related to growth development in early life may explain this outcome.…”
Section: Discussionmentioning
confidence: 96%
“…Other studies indicated that having a larger number of siblings was associated with a more signi cant decrease in BMI [18,32]. One study, however, reported that there was no association between the number of siblings and thinness [24], whereas another study found that thinness was more common in girls than in boys [23]. One possible explanation is the effect of behavior and interaction among family members.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation